Analisis Penerapan PSAK No. 18 Pada Laporan Keuangan PT. Bank BNI (Persero) - Nurfitriana, Nurfitriana; Efrianti, Desi (Institut Bisnis dan Informatika Kesatuan, 2018)
Financial Institution Pension Fund Bank BNI is one of the Banks that organizes a Defined Contribution Pension Program with the main activity of holding a Pension Program whose contribution amount is determined based on the ability of participants. The Pension Program organized by the Financial Institution Pension Fund (DPLK) of BNI provides pension benefits that will be received after participants enter retirement age based on the amount of the contribution, length of participation and the rate of growth of funds during the membership period. Pension benefits are paid on a pension basis with cash refund. As a Pension Fund company, PT. Bank Negara Indonesia (Persero) must refer to the provisions / regulations / standards in the determination and management of pension funds specifically PSAK No. 18 governing the retirement benefit program. Presentation of Retirement Benefit Programs in Pension Fund Financial Reports in 2012-2013 PT. Bank Negara Indonesia (Persero) is in accordance with the Statement of Accounting Standards (PSAK) No. 18. Therefore, this study aims to determine the suitability of the application of Financial Accounting Standard Number 18 on the Reporting of Bank Negara Indonesia Pension Fund (Persero). Keywords: pension fund accounting, PSAK no. 18.